2003
DOI: 10.1097/00004032-200310000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Tumors and Other Diseases Following Childhood X-Ray Treatment for Ringworm of the Scalp (Tinea Capitis)

Abstract: The objective of the study is to characterize the risk of tumors from radiation exposure to the head and neck. A cohort of 2,224 children given x-ray treatment and 1,380 given only topical medications for ringworm of the scalp (tinea capitis) during 1940-1959 have been followed up for a median of 39 y to determine tumor incidence. Follow-ups were by mail/telephone questionnaire, with 84-88% of the original cohort followed and with medical verification of diseases of interest. Sixteen intracranial tumors [7 bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 19 publications
1
24
0
5
Order By: Relevance
“…Although the doses to the thyroid gland in the Israeli tinea capitis study were low, averaging 90 mGy (range, 40 -500 mGy), they were very uncertain, and Ron et al (43) point out that only minor dosimetric adjustment in this cohort is required to make the ERR compatible with that in the other four studies. No significant thyroid cancer excess was observed in a much smaller U.S. group of patients given similar treatment (average thyroid dose, 60 mGy) (44), but the difference in risk estimates between this study and the comparable Israeli study was not statistically significant (44). Two Swedish studies of patients with skin hemangioma with low-dose and low dose rate exposures to radium 226 obtained risk estimates that were similar to those in the pooled analysis of Ron et al (43): an ERR per gray of 7.5 (95% CI: 0.4, 18.1) on the basis of an estimated mean thyroid dose of 120 mGy (45) and an ERR per gray of 4.9 (95% CI: 1.3, 10.2) on the basis of a mean dose of 260 mGy (46).…”
Section: Controversies: Linearity Of Risks Of Ionizing Radiationmentioning
confidence: 90%
“…Although the doses to the thyroid gland in the Israeli tinea capitis study were low, averaging 90 mGy (range, 40 -500 mGy), they were very uncertain, and Ron et al (43) point out that only minor dosimetric adjustment in this cohort is required to make the ERR compatible with that in the other four studies. No significant thyroid cancer excess was observed in a much smaller U.S. group of patients given similar treatment (average thyroid dose, 60 mGy) (44), but the difference in risk estimates between this study and the comparable Israeli study was not statistically significant (44). Two Swedish studies of patients with skin hemangioma with low-dose and low dose rate exposures to radium 226 obtained risk estimates that were similar to those in the pooled analysis of Ron et al (43): an ERR per gray of 7.5 (95% CI: 0.4, 18.1) on the basis of an estimated mean thyroid dose of 120 mGy (45) and an ERR per gray of 4.9 (95% CI: 1.3, 10.2) on the basis of a mean dose of 260 mGy (46).…”
Section: Controversies: Linearity Of Risks Of Ionizing Radiationmentioning
confidence: 90%
“…Recently, we showed that the highest risk for thyroid cancer among those exposed to radioactive iodines was for the youngest age group (0-5 years) (6). Studies of benign neoplasia after irradiation showed contradictory evidence, with some studies exhibiting no effects of age at exposure (13,19) and others a strong inverse effect (10,12). We estimated the highest excess relative risk for follicular adenoma for those exposed at 5-10 years (excess relative risk ¼ 3.34 per gray), although risk estimates for three age categories were not significantly different (p ¼ 0.60).…”
Section: Discussionmentioning
confidence: 99%
“…Little evidence exists to demonstrate that diagnostic X-ray exposure during childhood is a risk factor but therapeutic doses of X-rays have been associated with raised risks [Kuijten and Bunin, 1993]. The now-discontinued low dose radiation treatment of tinea capitis and skin disorders in children increases the risk of CNS tumours well into adulthood [Shore et al, 2003], as does radiotherapy for childhood cancers and leukaemia.…”
Section: Ionising Radiationmentioning
confidence: 99%